Determinants of Income of Poor Women-Headed Households in Madiun City - Sodik Dwi Purnomo (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2018)
This study is aimed to analyze the effect of the level of education, number of family members, age, number of work hours, and type of work against the income of poor woman as a head of family in the City of Madiun. Population in this research is poor household’s headed a poor women in the City of Madiun and in the sampling uses the slovin formula with the result of 98 poor households. The data analysis technique uses a multiple linear regression with Ordinary Least Square method (OLS). The analysis result showed that the level of education, number of family members, and the number of work hours has a positive and significant impact on the income of poor families while the age and type of work is not significantly effecting the income of poor women as heads of households in the City of Madiun.Keywords: Poverty, Haed of Household’s Women, Income, Education, Number of Family Member, Number of Work Hours, Type of Work.